2019
DOI: 10.1016/j.bpc.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mg2+-dependent, coaxial stacking rearrangements in a bulged three-way DNA junction by single-molecule FRET

Abstract: Three-way helical junctions (3WJs) arise in genetic processing, and they have architectural and functional roles in structured nucleic acids. An internal bulge at the junction core allows the helical domains to become oriented into two possible, coaxially stacked conformers. Here, the helical stacking arrangements for a series of bulged, DNA 3WJs were examined using ensemble fluorescence resonance energy transfer (FRET) and single-molecule FRET (smFRET) approaches. The 3WJs varied according to the GC content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Metal ions are involved in many critical biological processes, such as signal transduction and enzymatic activity. It is been found that metal–ions–dependent conformational changes play a critical role in the activities of proteins, DNA (DNAzymes [ 26 , 27 ] and Holliday junctions [ 39 , 40 ]), and RNA (ribozymes [ 41 ] and riboswitches [ 42 ]). The in vitro selected DNAzyme 39E has been isolated to have specificity to UO 2 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…Metal ions are involved in many critical biological processes, such as signal transduction and enzymatic activity. It is been found that metal–ions–dependent conformational changes play a critical role in the activities of proteins, DNA (DNAzymes [ 26 , 27 ] and Holliday junctions [ 39 , 40 ]), and RNA (ribozymes [ 41 ] and riboswitches [ 42 ]). The in vitro selected DNAzyme 39E has been isolated to have specificity to UO 2 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the four-way HJ (4WHJ), smFRET has also been applied in determining the conformational dynamics of three-way junction (3WJ, Figure 6 B). Leveille et al [ 92 ] first reported the application of smFRET in the helical stacking arrangement for a series of bulged-in DNA 3WJs. Moreover, replication slippage is a frequent reason for the emergence of 3WJs.…”
Section: Investigating the Structural Changes Under Various Circumstancesmentioning
confidence: 99%